ANALYSIS OF THE EXPORT-BASE COMMODITY SUPPLY ON THE ECONOMIC GROWTH IN ACEH, INDONESIA - Yahya .; Abubakar Hamzah; Mohd Nur Syechalad; Sofyan Syahnur (Aceh International Journal of Social Science, 2015)
The study aims to identify export base sectors and to analyse its impact to the economic growth based on the Cobb Douglas production function. Some relevant theories to support our arguments among others are base sector, export base and economic growth theory. Data of central government capital spending (CGB), local government capital spending (LGB), export average price (Pavg), provincial minimum wage (W) and linear multiple regression model is employed. The results show that the agriculture is the only basis sector in Aceh. The role of local government capital spending in the export based commodity supply contradicts the theory, provided indication that the local government capital spending has not been able to pull the economic growth. The role of central government capital spending, export average price and minimum wage have been in accordance with the available theoretical background. All independent variables are found to be statistically significant both partially and simultaneously, indicating that those variables are economically important to develop export base sectors in Aceh, however the impact on economic growth is relatively small. Keywords: export base sector, supply for export, economic growth, Aceh